Challenges for Compliance with Industrial Effluent Regulations—An Industry Perspective - Zulaikha Mokhtar; Steven Kenway; Irdayanti Mat Nashir (Challenges)
This study thoroughly examines the environmental challenges faced by Malaysian industries in adhering to industrial effluent regulations, addressing the question: what are the obstacles to compliance from the industry’s perspective? This study focuses on eight industries known for low environmental compliance over a seven-year period. Interviews with 13 stakeholders with combined operational experience of over 200 years were conducted to uncover barriers to compliance from the industry’s viewpoint. Key challenges identified include costs, employee attitudes, technology, management support, public complaints, and jurisdictional issues. The responses highlighted the complexity of compliance issues, ranging from divergent to unified viewpoints. According to respondents, enhancing compliance hinges on behavioral changes driven by awareness, incentives, enforcement, guidance, industry ratings, management commitment, and public disclosure of emissions data. This approach provides fresh practical insights that contribute to policy development, insights not previously documented in the literature. This study underscores the government’s crucial role in regulation adherence and the need to analyze barriers and explore alternative approaches. Understanding industry perspectives and strategies for continuous improvement is imperative. Therefore, analyzing current challenges and adopting adaptive measures are essential steps towards achieving self-compliance, continuous improvement, and ensuring environmental sustainability.